Availability of Quality Assurance Requirements in Higher Education Institutions in Libya: A Case Study of Institutional and Program Accreditation at the Colleges of Benghazi University (Journal of human and social sciences, 2026)
Higher education in both developed and developing countries has received significant attention, contributing to societal advancement by producing skilled, scientifically and professionally qualified graduates. Educational institutions aim to achieve quality to sustain themselves and satisfy students, their families, and faculty members. Implementing quality standards in education has become essential due to societal changes, technological progress, and the rapid expansion of knowledge. Effective quality assurance reflects the efficiency of the educational process and the institution’s ability to achieve its academic and behavioral objectives while fostering positive learning outcomes.Institutional and program accreditation has recently gained significant attention, as it directly affects the quality of educational outputs. Higher education institutions strive to enhance their academic standards, especially with growing competition among institutions, particularly in the private sector. In the Arab world, many universities face challenges in keeping pace with advancements, especially in modern technologies, making it essential to review and develop curricula and ensure graduate competencies. Applying quality assurance standards is critical to achieving accreditation, which requires meeting specific criteria that enable institutions to compete regionally and internationally.This study examines the availability of quality assurance requirements for institutional and program accreditation at the colleges of Benghazi University. Using a descriptive-analytical methodology, the research surveyed 136 academic and administrative staff to assess the implementation of quality assurance practices, identify gaps, and provide recommendations for improving educational standards and institutional performance.
Keywords: Quality Assurance; Institutional and Program Accreditation; Higher Education; Academic Accreditation Standards; Institutional Performance